Impact of immersion in papaya juice on color and surface roughness of nanohybrid composite resin - Constantia, Queenie Renata; Tjandrawinata, Rosalina; Putri, Tansza Setiana (Faculty of Dentistry, Universitas Gadjah Mada, 2024)
Nanohybrid composite resin is well-known because of its good aesthetic properties. It has high water sorption, allowing various coloring substances such as papaya juice to penetrate. Papaya juice enzymes may also cause a rougher composite resin surface. This study determined the effect of papaya juice on color and surface roughness of nanohybrid composite resin using laboratory experiment. This study used posttest with control group design containing 27 samples of nanohybrid composite resin (B & E Korea XS-FIL A3.5) with diameter of 10 mm and thickness of 2 mm. The samples were divided into 3 groups: immediate, control, and treatment group. The samples of immediate group were tested directly for color and surface roughness. The treatment group was immersed in papaya juice for 3 hours followed by 21 hours in distilled water, while the control group was immersed in distilled water for 24 hours. All samples were immersed in an incubator at 37 °C for 4 days. Changes in color and surface roughness were tested using a VITA Easyshade V spectrophotometer and a Taylor Hobson surface roughness tester, respectively. ANOVA and post hoc Tukey showed a significant (p < 0.05) change in color (p = 0.003) and surface roughness (p = 0.000); significant (p = 0.033) color change was obtained between the immediate group (E = 6.933) and the treatment group (E = 7.959). In terms of surface roughness, significant (p = 0.000) results were obtained between the treatment group (Ra = 1.974 μm) with the immediate group (Ra = 1.411 μm) and the control group (Ra = 1.404 μm). In conclusion, papaya juice causes changes in color and surface roughness of nanohybrid composite resin.